Competition and Efficiency in health care: an analysis of the Italian case - Roberto Cellini; Giacomo Pigatario; Ilde Rizzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
In this paper, we look at the Italian National Health System as a case study, in order to investigate whether competition exerts positive effect on the efficiency of the system. Using the DEA technique we measure the efficiency of accredited hospital production at the regional level; secondly, we take a cross-section regression analysis approach to analyse the determinants of efficiency. A general conclusion stemming out of the analysis is that competition is not a value per se and that its effects on the performance of the system are affected by the rules governing it.
Keywords: 330